ADHD : Attention-Deficit Hyperactivity Disorder in Children, Adolescents, and Adults. - Wender, Paul H. (Oxford University Press, USA, 2001)
Paul Wender began his career treating children with ADHD 37 years ago and has treated adults with the disorder for almost 30 years. His exhaustive research and insight gained from clinical practice led to the first book about ADHD in children (Minimal Brain Dysfunction in Children, 1971). Continuing research revealed that in many instances ADHD persisted into adult life, and that adult ADHD included symptoms that were not present in childhood. These findings resulted in his 1995 book Attention Deficit Hyperactivity Disorder in Adults. He also authored the first book for the parents of children.